2011
DOI: 10.1111/j.1759-3441.2011.00095.x
|View full text |Cite
|
Sign up to set email alerts
|

Does the Political Institution Matter for Financial Development?

Abstract: The study examines the effect of economic institutions on financial development, where economic institutions themselves are endogenous and determined by political power. Following the theory of “economic institution” proposed by Acemoglu et al. (2004), two groups of political power (de jure political power or political institution and de facto political power or distribution of resource) are employed in the analysis. By using the panel data of sixty counties during 1980–2006, the empirical results show that po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…In line with this view, the rule of law and the absence of corruption ensure accountability and stability in the financial sector. Substantial property rights and an effective legal system will eventually result in overall economic and financial development (Voghouei et al, 2011). Finally, greater institutional quality within a financial system provides better financial liberalization (Delis, 2012;Gazdar & Cherif, 2015).…”
Section: Institutional Quality and Bank Stabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…In line with this view, the rule of law and the absence of corruption ensure accountability and stability in the financial sector. Substantial property rights and an effective legal system will eventually result in overall economic and financial development (Voghouei et al, 2011). Finally, greater institutional quality within a financial system provides better financial liberalization (Delis, 2012;Gazdar & Cherif, 2015).…”
Section: Institutional Quality and Bank Stabilitymentioning
confidence: 99%
“…In our study, institutional quality is evaluated to measure banks' risky behavior, while emphasizes institutional quality as an aspect that affects the relationship between competition and bank stability. It is relevant to the suggestions of previous studies that have shown such an essential role for institutional quality (Delis, 2012;Voghouei et al, 2011).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…A large number of studies investigate institutional factors as determinants of financial development (Chinn and Ito ; Law and Habibullah ; Huang ; Voghouei, Azali and Law ; Le, Kim and Lee ). However, this study offers a new perspective on this issue.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of political regimes, as well as the economic model of capital market development, have been frequently investigated by researchers [e.g., Keefer 2007;Voghouei, Azali and Law 2011;Francis and Ofori 2015], and it is clear that in the Polish context, these items were crucial. What is more, politics drive regulations, governance standards, market practices, investment climate and the rules for those who run the businesses.…”
Section: Capital Market Developments In Polandmentioning
confidence: 99%